2002
DOI: 10.1104/pp.014951
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Sequence Analysis of the Sorghum RphRegion and the Maize Rp1 Resistance Gene Complex

Abstract: A 268-kb chromosomal segment containing sorghum (Sorghum bicolor) genes that are orthologous to the maize (Zea mays) Rp1 disease resistance (R) gene complex was sequenced. A region of approximately 27 kb in sorghum was found to contain five Rp1 homologs, but most have structures indicating that they are not functional. In contrast, maize inbred B73 has 15 Rp1 homologs in two nearby clusters of 250 and 300 kb. As at maize Rp1, the cluster of R gene homologs is interrupted by the presence of several genes that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 64 publications
(40 reference statements)
0
37
1
Order By: Relevance
“…This finding largely reflects difficulties in distinguishing among different members of gene families or between duplicated genes. The best evidence for orthology is obtained by sequencing and comparative analysis of orthologous BAC clones from multiple grass species; however, few such comparisons have been performed to date (Chen et al, 1998;Tikhonov et al, 1999;Tarchini et al, 2000;Morishige et al, 2002;Ramakrishna et al, 2002aRamakrishna et al, , 2002bSong et al, 2002). As demonstrated in our surveys for conserved sequence blocks among both maize-rice and maizesorghum gene pairs, blocks of Ͼ70% identity over a window of 20 bp are likely to be found only among orthologous genes.…”
Section: An Annotated Database For Cereal Gene Promoter Sequencesmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding largely reflects difficulties in distinguishing among different members of gene families or between duplicated genes. The best evidence for orthology is obtained by sequencing and comparative analysis of orthologous BAC clones from multiple grass species; however, few such comparisons have been performed to date (Chen et al, 1998;Tikhonov et al, 1999;Tarchini et al, 2000;Morishige et al, 2002;Ramakrishna et al, 2002aRamakrishna et al, , 2002bSong et al, 2002). As demonstrated in our surveys for conserved sequence blocks among both maize-rice and maizesorghum gene pairs, blocks of Ͼ70% identity over a window of 20 bp are likely to be found only among orthologous genes.…”
Section: An Annotated Database For Cereal Gene Promoter Sequencesmentioning
confidence: 91%
“…This observation suggests that A1-b is more likely to be orthologous with the maize a1 gene than with sorghum A1-a. Similarly, VISTA comparisons of the maize Rp1-D gene with the different duplicated sorghum rph1 genes characterized by Ramakrishna et al (2002b) found that maize Rp1-D showed CNS only with the sorghum rph1-1 gene promoter region (data not shown), despite the fact that the rph1-1 coding region is truncated. This finding suggests that maize Rp1-D and sorghum rph1-1 may be orthologous genes that subsequently underwent independent duplication and diversification in the maize and sorghum lineages.…”
Section: An Annotated Database For Cereal Gene Promoter Sequencesmentioning
confidence: 99%
“…In general, large multigene families, such as disease resistance genes and genes involved in reproduction or morphological complexity, evolve rapidly (Leister et al, 1998;Meyers et al, 1999;Song et al, 2001;Ramakrishna et al, 2002aRamakrishna et al, , 2002bSong and Messing, 2002;Fiebig et al, 2004;Schein et al, 2004). The frequent gain and loss of gene family members observed in this region follows the birth-and-death model of gene evolution (Ohno, 1970;Nei et al, 1997;Michelmore and Meyers, 1998;Nei and Rooney, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative sequence analysis of a resistance gene complex in sorghum and maize shows that disease resistance gene clusters are unusually prone to frequent internal and adjacent chromosomal rearrangements (Ramakrishna et al, 2002). Such rearrangements may facilitate the rapid evolution of these genes and, in turn, help plants develop novel resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%